Anonymous Power Parties, Interest Groups and Politics of Decision Making in Nigeria’s Fourth Republic (Essays in Honour of Elochukwu Amucheazi) - Ibeanu, Okechukwu; Okoye, Israel 'Kelue; Alumona, Ikenna Mike; Aniche, Ernest Toochi (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
XXVIII, 497 p. 6 illus.